Socioeconomic patient characteristics predict delay in cancer diagnosis: a Danish cohort study - Sokolowski Ineta; Sørensen Henrik; Olesen Frede; Hansen Rikke; Søndergaard Jens (BMC, 2008)
Abstract Background Delay in cancer diagnosis may be important for cancer prognosis. Large individual variations in the duration of delay have been observed. This study examines whether patients' socioeconomic characteristics are predictors of long patient-, doctor- and system-related delay in cancer diagnosis. Methods Danish population-based cohort study. From September 2004 to September 2005, newly diagnosed cancer patients were enrolled from administrative registries. A total of 467 general practitioners in the County of Aarhus, Denmark, completed questionnaires on 2,212 cancer patients' diagnostic pathways. A total of 1,252 cancer patients filled in questionnaires on their socioeconomic characteristics (e.g. marital status, education, occupation, household income and fortune). Delay was categorised as short or long based on quartiles. Predictors of long delay were assessed in a logistic regression model using odds ratios (ORs) as a proxy of relative risks. Results In regard to patient delay, retired female patients experienced shorter delays (OR 0.35, 95% confidence interval (95%CI) 0.13 to 0.98) than employed female patients, while female smokers experienced longer delays (OR 2.42, 95%CI 1.21 to 4.85) than female non-smokers. In regard to doctor delay, female patients with a large household fortune experienced shorter delays (OR 0.07, 95%CI 0.01 to 0.45) than economically less privileged female patients. Well-educated men experienced shorter delays (OR 0.40, 95%CI 0.16 to 1.00) than men with short education. Male patients experienced longer doctor delays (OR 2.11, 95%CI 1.11 to 4.02) than women when gender-specific cancers were excluded. In regard to system delay, female patients with a large household fortune experienced shorter delays (OR 0.46, 95%CI 0.21 to 0.99) than economically less privileged women, while female patients with a high alcohol intake experienced longer delays (OR 2.82, 95%CI 1.18 to 6.72) than women with an average intake. Conclusion We found socioeconomic predictors of delay that allow us to hypothesize social inequalities in the distribution of delay, but, in general, only a few socioeconomic variables predicted delay in cancer diagnosis. Future research should examine a broader array of patients' personal characteristics.